TRACES OF MUSICAL INSTRUMENTS IN KAKAWIN BHARATAYUDHA - Santosa, Hendra; Kustiyanti, Dyah; Sudirga, I Komang (E-Journal of Cultural Studies, 2017)
This article is part of the research entitled " Melacak Jejakdari Karawitan dalam Naskah JawaKuno: Kajian Bentuk, Fungsi, dan Makna " based on 22 early Old Javanese literature manuscripts.This article is specifically talking about the form and function of musical instruments that are written in the Kakawin Bratayudha only to clarify the form and function of musical instruments during the reign of Jayabaya in Kediri, East Java. This study uses historical method, namely, through the stages of heuristics, criticism, interpretation, and historiography. The results showed that at the stage of heuristics three kakawin are found including Bharatayudha by I WayanWarna in 1990, works of R.M. SutjiptoWirjosuparto 1968 entitled Kakawin BharataYudha, and a translation book Kakawin BharataYudha by I Gusti Bagus Sugriva, 2012. Criticism is done internally through translation and also by comparing the three works from the text, followed by interpretation of the translation of three Kakawin BharataYudha , and the last is the stage of historiography. The function of musical instruments in the kakawin of BharataYudha can not be separated from the function of musical instruments at the time of the Ancient Javanese namely as a means of ceremonies and to accompany secular activities. Secular activity in question is entertainment, communication, respect, war, economy, dowry, and symbol (Fernandus, 2003: 381-415). Musical instruments contained in kakawin BharataYudha , is still found, but there also have been renamed as Mredangga (drum) and rawanahasta (a type of fiddle). Harps only thrive in Sundanese, and Rawanahasta grow and spread in different parts of the archipelago.